AI-Powered Cloud Storage: A Complete Review of Efficiency Improvements - Abbas, Leila (MZ Journal of Artificial Intelligence, 2024)
AI-powered cloud storage represents a significant leap forward in digital storage solutions, integrating artificial intelligence algorithms to enhance efficiency and usability. This comprehensive review explores the advancements and benefits of AI-driven systems in cloud storage environments. These systems automate file organization, optimize storage allocation, and improve data retrieval speeds by leveraging machine learning. Additionally, AI algorithms analyze usage patterns to predict future storage needs, ensuring scalability and cost-effectiveness. Security features are also bolstered through AI, with real-time threat detection and adaptive access controls. This review examines how AI-powered cloud storage streamlines operations and sets a new standard for reliability, performance, and data management in modern IT infrastructures.